Optimasi Penggunaan Manipulator pada Sensor O2 Untuk Menaikkan Performa Scooter Dengan Mode Transmisi Matic 4 Langkah - ridzal; Wegie Ruslan (Magister Teknik Mesin Universitas Pancasila, 2020)
Technological developments, especially in the automotive industry, have experienced rapid development, this can be seen in the production of motorbikes, where many users really want the performance of their vehicles. This research is a different solution from previous studies that have been done before, where previous research replaced the O2 sensor with a manipulator, this research was carried out by keeping the O2 sensor installed, only in pairs of resistors. So that the O2 sensor output voltage can be manipulated before being accepted by the ECU. The voltage at the output can be manipulated by providing a resistance on the O2 sensor which previously went to the Electronic Control Unit, by adding several resistance variables which are valued between 0.5 ggt`6Ohm up to a value of 2 Ohm. Retrieval of data to be able to perform testing techniques on engine performance, namely by using the Dynojet Chassis technique, with the addition of several variables for engine speed, starting from a variable of 3000 rpm to 9000 rpm, so as to be able to find out how much value is in the role of change The output of electric current on the oxygen sensor, namely the torque and power in the sample used in this study, is a scooter with a 4-step automatic transmission mode. Based on several parameters generated from the test along with the analysis results from data processing, the conclusion of this study is that the use of a manipulator on the O2 sensor can actually be used to increase the performance of a scooter with a 4-step automatic transmission mode